Nano-fibers fabrication using biological macromolecules: Application in biosensing and biomedicine - Darshna; Dkhar D.S.; Srivastava P.; Chandra P. (My University, 2025)
Nanofibers, a type of nanomaterial, have been widely use in a variety of fields, both research and commercial applications. They are a material of choice in a diverse range of applications due to their characteristics and unique physicochemical properties. Nanofibers have cross-sectional dimeters varying between 1 nm and 100 nm, the nano range dimensions providing them characteristics such as high surface area-to-volume ratio, highly porous as well as interconnected networks. There are various types of materials which have been used to synthesize nanofibers both biological (namely, hyaluronic acid, chitosan, alginate, fibrin, collagen, gelatin, silk fibroin, gums, and cellulose) as well as synthetic (namely, poly(lactic acid), poly(1-caprolactone), poly(vinyl alcohol), and polyurethane) polymers which have been briefly discussed in the present review. The review also explores various fabrication techniques for producing nanofibers, such as physical/chemical/biological techniques as well as electrospinning/non-spinning techniques. Due to their distinctive physicochemical qualities, nanofibers have become intriguing one-dimensional nanomaterials with applications in a wide range of biomedical fields. In line with this, the review discusses about various applications of nanofibers, namely, wound dressing, drug delivery, implants, diagnostic devices, tissue engineering, and biosensing. Furthermore, having an insight of the distinctive characteristics of nanofibers materials which could have immense potential in various biosensing applications, this review emphasizes on application of nanofibrous materials in the field of biosensing. However, despite these advances, there remain some challenges that need to be addressed before nanofiber technology can be widely adopted for its commercial use in biomedical as well as biosensing applications. © 2025 Elsevier B.V.